MANAJEMEN DAN PENDISTRIBUSIAN ZAKAT DALAM UPAYA PENINGKATAN KESEJAHTERAAN SOSIAL MASYARAKAT - Nur Afni (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2020)
The management of zakat in relation to economic empowerment means that zakat as an asset of an Islamic economic institution, zakat is a source of strategic potential funds for efforts to build the welfare of the people. Because of that, the Koran gives a sign that the zakat collected is managed appropriately and effectively. The purpose of this research is to describe how the management and distribution of zakat to improve the social welfare of society. The type of research used in this research is library research or library research conducted by collecting data or scientific papers aimed at the research object. The results of the discussion in the article are; 1) in the process of managing zakat, it can be realized seriously, of course, this needs to be supported by good management, as was done in the early days of Islam. Managing zakat effectively and efficiently needs to be managed properly. Therefore, the management of zakat provides the application of modern management functions. 2) Zakat must be distributed to mustahik under Islamic law. 3) the distribution of zakat is carried out based on a priority scale, with due observance of the principles of equity, justice, and territoriality, and 4) Zakat is distributed through two distribution models directly or consumptive zakat, and indirect distribution, namely productive zakat.